Contractile vacuoles: a rapidly expanding (and occasionally diminishing?) understanding - More, Kiran J; Kaur, Harpreet; Simpson, Alastair G B; Spiegel, Frederick W; Dacks, Joel B (European journal of protistology, 2024)
Osmoregulation is the homeostatic mechanism essential for the survival of organisms in hypoosmotic and hyperosmotic conditions. In freshwater or soil dwelling protists this is frequently achieved through the action of an osmoregulatory organelle, the contractile vacuole. This endomembrane organelle responds to the osmotic challenges and compensates by collecting and expelling the excess water to maintain the cellular osmolarity. As compared with other endomembrane organelles, this organelle is underappreciated and under-studied. Here we review the reported presence or absence of contractile vacuoles across eukaryotic diversity, as well as the observed variability in the structure, function, and molecular machinery of this organelle. Our findings highlight the challenges and opportunities for constructing cellular and evolutionary models for this intriguing organelle.
Keywords: Membrane-trafficking; Organelle; Ciliate; Osmoregulation; Evolution; Vacuoles; vakuoly; Eukaryota; osmoregulace; Endosome